Feasibility and potential efficacy of a guided internet- and mobile-based CBT for adolescents and young adults with chronic medical conditions and comorbid depression or anxiety symptoms (youthCOACHCD): a randomized controlled pilot trial - A. Geirhos; M. Domhardt; F. Lunkenheimer; S. Temming; R. W. Holl; K. Minden; P. Warschburger; T. Meissner; A. S. Mueller-Stierlin; H. Baumeister (BMC, 2022)
Abstract Background Adolescents and young adults (AYA) with a chronic medical condition show an increased risk for developing mental comorbidities compared to their healthy peers. Internet- and mobile-based cognitive behavioral therapy (iCBT) might be a low-threshold treatment to support affected AYA. In this randomized controlled pilot trial, the feasibility and potential efficacy of youthCOACHCD, an iCBT targeting symptoms of anxiety and depression in AYA with chronic medical conditions, was evaluated. Methods A total of 30 AYA (M age 16.13; SD= 2.34; 73% female), aged 12-21 years either suffering from cystic fibrosis, juvenile idiopathic arthritis or type 1 diabetes, were randomly assigned to either a guided version of the iCBT youthCOACHCD (IG, n=15) or to a waitlist control group (CG, n=15), receiving an unguided version of the iCBT six months post-randomization. Participants of the IG and the CG were assessed before (t0), twelve weeks after (t1) and six months after (t2) randomization. Primary outcome was the feasibility of the iCBT. Different parameters of feasibility e.g. acceptance, client satisfaction or potential side effects were evaluated. First indications of the possible efficacy with regard to the primary efficacy outcome, the Patient Health Questionnaire Anxiety and Depression Scale, and further outcome variables were evaluated using linear regression models, adjusting for baseline values. Results Regarding feasibility, intervention completion was 60%; intervention satisfaction (M = 25.42, SD = 5.85) and perceived therapeutic alliance (M = 2.83, SD = 1.25) were moderate and comparable to other iCBTs. No patterns emerged regarding subjective and objective negative side effects due to participation in youthCOACHCD. Estimates of potential efficacy showed between group differences, with a potential medium-term benefit of youthCOACHCD (β = -0.55, 95%CI: -1.17; 0.07), but probably not short-term (β = 0.20, 95%CI: -0.47; 0.88). Conclusions Our results point to the feasibility of youthCOACHCD and the implementation of a future definitive randomized controlled trial addressing its effectiveness and cost-effectiveness. Due to the small sample size, conclusions are premature, however, further strategies to foster treatment adherence should be considered. Trial registration The trial was registered at the WHO International Clinical Trials Registry Platform via the German Clinical Trials Register (ID: DRKS00016714 , 25/03/2019).